Modelagem para mensuração da inovação no setor de construção naval e offshore brasileiro - Dickel, Deise Graziele (2015)
The oil discoveries in Brazilian pre-salt began a strong mobilization of government and also private companies to the rescue of the shipbuilding industry in the country. With the objective to become the Brazilian industry globally competitive, various government incentives provided growth, expansion and modernization of this industry that already ranks fourth in the ranking of the largest craft producing countries of the world. In this context, despite not being a young industry in Brazil, shipbuilding, especially focused on oil exploration (offshore) proved to be important element for the growth of the economy, creating jobs, developing producing regions and boosting the entire chain productive. Despite the favorable environment in which shipbuilding and offshore industries are, there are still gaps that undermine competitiveness these organizations in the global market, as the skilled labor available, the adequacy of suppliers to their demands and the large need for investment in technology. Thus, this dissertation project aims at proposing a model able to measure the level of innovation in Brazilian shipbuilding and offshore, in the structural and business fields, based on a literature and documentary research on the characteristics of the industry sector, using for both assumptions regarding the Key Performance Indicators (KPIs) and the concepts of multi-criteria decision aid. The proposed model will be put to test in real companies, returning in its evaluation phase an index that represents the competitive performance of each industry evaluated, thus allowing comparison and discussion of the results. Subsequently, will be proposed recommendations able to leverage the innovation of those who submit the most unsatisfactory levels, thus demonstrating the relevance of modeling to increase the sector's competitiveness against the scenario that presents itself.